Ultrasound enhances the therapeutic potential of mesenchymal stem cells wrapped in greater omentum for aristolochic acid nephropathy - Yang, Yuanjun (Stem Cell Res Ther, 2021)
BACKGROUND: Mesenchymal stem cells (MSCs) have been reported to promote regeneration in both subjects with acute kidney injury (AKI) and chronic kidney disease (CKD), but their efficacy remains limited, probably because most of the cells accumulate in the lungs, liver, and spleen after an intravenous infusion. Therefore, ultrasound-guided administration of MSCs represents a possible approach to solve this problem. The greater omentum is used to promote cell survival due to its rich vasculature. We hypothesized that ultrasound-guided administration of MSCs combined with greater omentum might be more curative than currently available approaches. METHODS: In this study, we established an aristolochic acid nephropathy (AAN) model by intraperitoneally administering aristolochic acid I sodium salt (AA-I) at a dose of 5 mg/kg body weight on alternate days for 4 weeks. Subsequently, a laparotomy was performed, and the left kidney from which the capsule had been removed was wrapped with the greater omentum. A dose of 2 × 10(7) MSCs was injected into the space between the greater omentum and the left kidney. Equal amounts of MSCs were administered under ultrasound guidance every second week for a total of 4 treatments. Mice were sacrificed 4 weeks after surgery. Serum creatinine and blood urea levels were measured to assess renal function. qPCR, Western blot, and histological analyses were conducted to further investigate the therapeutic mechanism of MSCs. RESULTS: Ultrasound-guided injection of MSCs into the greater omentum that surrounds the kidney enriched cells in the kidney region for up to 5 days. Renal function tests indicated that MSCs improved renal function to a great extent, as reflected by decreased blood urea nitrogen and serum creatinine levels. In addition, histological analyses showed that MSCs noticeably attenuated kidney injury, as evidenced by the amelioration of tubular necrosis and peritubular interstitial fibrosis. Mitigation of renal interstitial fibrosis was further confirmed by immunohistochemistry, qPCR, and western blotting after MSC treatment. Moreover, immunofluorescence staining revealed that MSCs alleviated inflammatory responses by increasing the counts of CD206+ cells and decreasing the counts of CD68+ cells. MSC migration was initiated in response to AA-I-treated renal epithelial cells in an in vitro migration assay. CONCLUSIONS: These findings suggested that administration of MSCs into the cavity formed by the injured kidney and the greater omentum under ultrasound guidance improved renal function, attenuated kidney injury, and mitigated renal interstitial fibrosis and inflammatory responses. Thus, this approach might be a safe and effective therapy for CKD. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13287-021-02243-7.